Effect of Growth Rate and Starvation-Survival on Cellular DNA, RNA, and Protein of a Psychrophilic Marine Bacterium - Moyer, Craig L. (1989)
DNA, RNA, and protein concentrations from starved ANT-300 cell populations grown at different growth rates fluctuated corresponding to the three stages of starvation-survival on total and viable cell bases. During stage 1 of starvation-survival, two to three peaks in the concentration levels for all three macromolecules were characteristic. During stage 2, DNA per total cell dropped to between 4.2 and 8.3% of the original amount for all of the cell populations examined, and it stabilized throughout stage 3. The decrease in DNA per cell was also observed in electron micrographs of cellular DNA in unstarved compared with starved cells. The fluctuations of RNA and protein per total cell concentrations observed during stage 2 coincided in all cases, except for the cells from dilution rate (D) = 0.015 h(−1). This ANT-300 cell population showed a decrease in RNA per total cell to only 29.2% and an increase in protein to 129.7% of the original amount after 98 days of starvation. During stage 3, DNA, RNA, and protein concentrations per total cell also stabilized to continuous levels. Cells from the faster-growth-rate cell populations of D = 0.170 h(−1) and batch culture had elevated protein per total cell concentrations, which remained primarily residual during the starvation period. Starved cells from D = 0.015 h(−1) had estimated nucleoid and cell volumes of 0.018 and 0.05 μm(3), respectively, yielding a nucleoid volume/cell volume ratio of 0.40. We consider these data to indicate that slow-growth-rate cells are better adapted for starvation-survival than their faster-growth-rate counterparts.